Oral L-Arginine Supplementation Effects on Cardiometabolic Factors in Hypertensive Patients with Rheumatoid Arthritis and its Relationship with Body Mass Index - Kuryata, Olexandr; Sirenko, Oksana (Journal of Nutritional Therapeutics, 2015)
Hypertension and rheumatoid arthritis are regarded as a conditions associated with higher risk for cardiovascular disease. As known endothelial dysfunction is an early pathophysiological feature and an independent predictor cardiovascular disease. L-arginine is the amino acid with potential to improve endothelial function and is expected to play a role in the prevention or treatment of cardiovascular disease. In addition, data exists that L-arginine aspartate can reduce insulin resistance. We aimed to evaluate the effects of oral L-arginine supplementation on cardiometabolic factors by determining endothelial function, insulin resistance, adiponectin level in hypertensive patients combined with rheumatoid arthritis and its relationship with body mass index. 69 females with mean age – 54 [50,3; 61,5] years were enrolled. The 1st group made up 29 patients with hypertension combined with rheumatoid arthritis, 2nd group – 20 patients with rheumatoid arthritis, 3rd group – 20 patients with hypertension. In the endpoint patients were randomized to study subgroups patients, which received L-Arginine aspartate 30 ml/day during 4 weeks in addition to standard treatment, and control subgroups – received only the standard treatment. The levels of total cholesterol, triglycerides, C-reactive protein, serum creatinine, body mass index, body area index were determined. Insulin resistance, adiponectin level, endothelial-dependent flow mediated vasodilatation of brachial artery were measured at baseline and after 4 weeks. In patients with hypertension combined with rheumatoid arthritis identified a significant increase in insulin levels, insulin resistance, adiponectin, which were associated with cardiovascular risk, abdominal obesity, inflammatory activity levels. Oral supplementation of L-arginine causes multiple beneficial effects on the complex of cardiometabolic factors including: endothelial dysfunction, peripheral insulin resistance, adiponectin level in hypertensive patients with rheumatoid arthritis, mainly in obesity case. With the correction of endothelial function were established more significantly changes in the investigated parameters.